Regulation Mechanisms of Expression and Function of Organic Cation Transporter 1 - Ciarimboli, Giuliano (Frontiers in Pharmacology, 2021)
The organic cation transporter 1 (OCT1) belongs together with OCT2 and 3 to the solute carrier family 22 (SLC22). OCTs are involved in the movement of organic cations through the plasma membrane. In humans, OCT1 is mainly expressed in the sinusoidal membrane of hepatocytes, while in rodents OCT1 is strongly represented also in the basolateral membrane of renal proximal tubule cells. Considering that organic cations of endogenous origin are important neurotransmitters and that those of exogenous origin are important drugs, these transporters have significant physiological and pharmacological implications. Because of the high expression of OCTs in excretory organs, their activity has the potential to significantly impact not only local but also systemic concentration of their substrates. Even though many aspects governing OCT function, interaction with substrates, and pharmacological role have been extensively investigated, less is known about regulation of OCTs. Possible mechanisms of regulation include genetic and epigenetic modifications, rapid regulation processes induced by kinases, regulation caused by protein-protein interaction, and long-term regulation induced by specific metabolic and pathological situations. In this mini-review, the known regulatory processes of OCT1 expression and function obtained from in vitro and in vivo studies are summarized. Further research should be addressed to integrate this knowledge to known aspects of OCT1 physiology and pharmacology.